Molecular dynamics simulation study of gold nanosheet as drug delivery vehicles for anti-HIV-1 aptamers. (December 2021) - Ajamgard, Marzieh; Sardroodi, Jaber Jahanbin; Ebrahimzadeh, Alireza Rastkar; Kamelabad, Mahrokh Rezaei
Abstract: The adsorption process of three aptamers with gold nanosheet (GNS) as a drug carrier has been investigated with the help of molecular dynamics simulations. The sequencing of the considered aptamers are as (CUUCAUUGUAACUUCUCAUAAUUUCCCGAGGCUUUUACUUUCGGGGUCCU) and (CCGGGUCGUCCCCUACGGGGACUAAAGACUGUGUCCAACCGCCCUCGCCU) for AP1 and AP2, respectively. AP3 is a muted version of AP1 in which nucleotide positions 4, 6, 18, 28 and 39 have C4A, U6G, A18G, G28A, and U39C mutations. At positions 24, and 40, a deletion mutation is seen to eliminate U24 and U40 bases. These aptamers are inhibitors for HIV-1 protease and can be candidates as potential pharmaceutics for treatment of AIDS in the future. The interactions between considered aptamers and GNS have been analyzed in detail with help of structural and energetic properties. These analyses showed that all three aptamers could well adsorb on GNS. Overall, the final results show that the adsorption of AP2 on the GNS is more favorable than other considered ones and consequently GNS can be considered as a device in order to immobilize these aptamers. Graphical Abstract: ga1 Highlights: The adsorption process of three anti-HIV-1 aptamers (AP1, AP2, and AP3) on gold nanosheet (GNS) was simulated. There is no unexpected deformation in the aptamers structure. The van der Waals interactions played a main role in absorption process. The adsorption and immobilization of aptamer 2 on the GNS is more favorable than other considered ones. GNS can be considered as drug delivery vehicles in order to immobilize these aptamers.